Community Legal Education for Post-Covid-19: Economic Recovery and Crime Prevention Awareness (Case of Mokoau, Kendari Indonesia) - Herman, Herman; Dewa, Muhammad Jufri; Tatawu, Guasman; Rizky, Ali; Sulihin, La Ode Muhamad; Fikri, Hamdan (Universitas Negeri Semarang, 2023)
Crime prevention is an effort to provide protection to the community and realize the welfare of the community. The phenomenon that occurs in the people of Kendari City is not only the high number of street crimes, but also the potential for conflict in society. The high level of crime will greatly affect economic recovery efforts, especially after the Covid-19 pandemic. This community service aims to increase people's knowledge and understanding of the importance of preventing and overcoming crimes that occur in society. This service is carried out in two stages. First, identify legal problems that occur in the community, namely in Mokoau Village. As a result, the crime of theft and the behavior of consuming alcohol are crimes that often occur. Second, direct socialization to the community and conduct legal counseling related to crime prevention policies. At this stage, the public is given an understanding of the modus operandi of theft crime, strategies to prevent theft crime and the impact of alcohol consumption behavior in particular and the impact of crime in society in general. The results of this service show an increase in public knowledge and awareness of responsibility in preventing and overcoming crime. Residents who have very high understanding increased from 13% to 65%. Meanwhile, residents' low understanding of obligations and responsibilities in crime prevention and overcoming decreased from 47% to 13%. That all communities have the same roles and responsibilities in realizing peace and comfort in the community environment.